Occurrence of a new species of Letana (Orthoptera: Tettigoniidae: Phaneropterinae) in India - Nagar, Rajendra; Swaminathan, R. (Zootaxa, 2015)
A new species of the Oriental genus Letana, Walker (Orthoptera: Tettigoniidae: Phaneropterinae), proposed as Letana dentata sp. nov., collected from the North-eastern province, Meghalaya, India (Ri bhoi 90°55’15 to 91°16’ latitude and 25°40’ to 25°21’ longitude, 993 MSL), is described together with the morphological characterization of eight reported species. Of these, Letana rubescens (Stål, 1861) collected from Shalimar, Srinagar, Jammu and Kashmir (India) is being reported for the first time from India. The other species of Letana include: L. atomifera, L. bulbosa, L. inflata, L. infurcata, L. pyrifera and L. rufonatata. Taxonomic and diagnostic characters with illustrations of the head, pronotum, ventral view of left tegmina to show stridulatory file teeth and the genitalia (supra-anal plate and subgenital plate) including the phallus sclerite has been given.